2004
DOI: 10.1002/smj.403
|View full text |Cite
|
Sign up to set email alerts
|

Resource‐seeking agglomeration: a study of market entry in the lodging industry

Abstract: We analyze whether firms prefer collocating with incumbent firms when choosing among markets to enter, highlighting the role of resource-seeking as a motivation for collocation. We propose that entrants will locate near others possessing resources that can spill over, but will avoid locations where existing firms will exploit spillovers without contributing. To test these propositions, we analyze the location decisions of 570 new hotels in Texas between 1992 and 2000. We find that hotels are attracted to marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
210
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(239 citation statements)
references
References 30 publications
11
210
0
3
Order By: Relevance
“…The data can be downloaded at ͗http://www.window-.state.tx.us/ecodata/taxfiles.html#hotel͘. Conlin and Kadiyali (2006), Kalnins (2004), and Chung (2004, 2006) have described and analyzed these data. The 1,387 franchised hotels in Texas in 1999 were distributed across 536 zip codes, 351 of which have more than one hotel with a name brand.…”
Section: Market Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The data can be downloaded at ͗http://www.window-.state.tx.us/ecodata/taxfiles.html#hotel͘. Conlin and Kadiyali (2006), Kalnins (2004), and Chung (2004, 2006) have described and analyzed these data. The 1,387 franchised hotels in Texas in 1999 were distributed across 536 zip codes, 351 of which have more than one hotel with a name brand.…”
Section: Market Concentrationmentioning
confidence: 99%
“…In a further 187 cases, a firm operates one branded and one nonbranded hotel in the same zip code. On one dimension, however, industry concentration may be lower than it appears to a casual observer: franchisees are very willing to compete aggressively against others affiliated with the same brand, though these are typically found in neighboring markets rather than in the same market (Kalnins, 2004).…”
Section: Market Concentrationmentioning
confidence: 99%
“…This perspective, emphasized in studies published in recent decades (e.g. Chung, Kalnins 2001, Kalnins, Chung 2004, Marco-Lajara et al 2016, complements the classical demand perspective that considers the availability of resources demanded by tourists as the exclusive rationale behind the tourist companies location decisions. Accordingly, our paper aims to reveal their distribution and resulted spatial agglomerations in Romania, as a background for rational decisions regarding the support that will be offered to the most relevant tourism destinations as well as the measures meant to enhance collaborative networks and competitiveness in the tourism activity-based agglomerations, creating synergies that can increase economic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on the tourism sector have shown that these externalities also arise, finding a positive correlation between firm agglomeration and hotel profitability [7,11]. Moreover, other studies suggest that hotels tend to be located where other hotels already exist because it allows them to improve both their efficiency and their chances of survival [12][13][14][15].…”
Section: Agglomeration Economies In the Hospitality Industrymentioning
confidence: 99%